Mireille Delmas-Marty, Les droits de l’homme et le « pot au noir » (Prawa człowieka i „równikowy pas ciszy”1), „Communication” 2019, vol. 1, n° 104, pp. 25–36 - Krzanowski, Marcel (Studia Prawa Publicznego, 2023)
Mireille Delmas-Marty, Les droits de l’homme et le « pot au noir » (Prawa człowieka i „równikowy pas ciszy”1), „Communication” 2019, vol. 1, n° 104, pp. 25–36, https://doi.org/10.3917/commu.104.0025